An Inexpensive Bismuth-Petrolatum Dressing for Treatment of Burns. Issue 6 (June 2016) - Chattopadhyay, Arhana; Chang, Kathleen; Nguyen, Khoa; Galvez, Michael G.; Legrand, Anais; Davis, Christopher; McGoldrick, Rory; Long, Chao; Pham, Hung; Chang, James
Abstract : Background: Xeroform remains the current standard for treating superficial partial-thickness burns but can be prohibitively expensive in developing countries with prevalent burn injuries. This study (1) describes the production of an alternative low-cost dressing and (2) compares the alternative dressing and Xeroform using the metrics of cost-effectiveness, antimicrobial activity, and biocompatibility in vitro, and wound healing in vivo. Methods: To produce the alternative dressing, 3% bismuth tribromophenate powder was combined with petroleum jelly by hand and applied to Kerlix gauze. To assess cost-effectiveness, the unit costs of Xeroform and components of the alternative dressing were compared. To assess antimicrobial properties, the dressings were placed on agar plated with Escherichia coli and the Kirby-Bauer assay performed. To assess biocompatibility, the dressings were incubated with human dermal fibroblasts and cells stained with methylene blue. To assess in vivo wound healing, dressings were applied to excisional wounds on rats and the rate of re-epithelialization calculated. Results: The alternative dressing costs 34% of the least expensive brand of Xeroform. Antimicrobial assays showed that both dressings had similar bacteriostatic effects. Biocompatibility assays showed that there was no statistical difference ( P < 0.05) in the cytotoxicity of Xeroform, alternative dressing, and Kerlix gauze. Finally, the in vivo healing model showed no statistical difference ( P < 0.05) in mean re-epithelialization time between Xeroform (13.0 ± 1.6 days) and alternative dressing (13.5 ± 1.0 days). Conclusions: Xeroform is biocompatible, reduces infection, and enhances healing of burn wounds by preventing desiccation and mechanical trauma. Handmade petrolatum gauze may be a low-cost replacement for Xeroform. Future studies will focus on clinical trials in burn units.